Precuneus Dysfunction in Parkinson’s Disease With Mild Cognitive Impairment - Jia, Xiuqin; Li, Ying; Li, Kuncheng; Liang, Peipeng; Fu, Xiaolan (Frontiers in Aging Neuroscience, 2019)
Background: Mild cognitive impairment (MCI) frequently occurs in Parkinson's disease (PD). Neurovascular changes interact with neurodegenerative process in PD. However, the deficits of cerebral blood flow (CBF) perfusion and the associated functional connectivity (FC) in PD patients with MCI (PD-MCI) remain unclear. Purpose: This study aimed to explore the specific neurovascular perfusion alterations in PD-MCI compared to PD with normal cognition (PD-NC) and healthy controls (HCs), and to further examine the resultant whole brain FC changes in the abnormal perfusion regions. Methods: Relative cerebral blood flow (rCBF) was calculated using arterial spin labelling (ASL) in 54 patients with PD (27 patients with PD-NC and 27 patients with PD-MCI) and 25 HCs matched for age and gender ratio, who also underwent the structural MRI, resting-state functional MRI (rs-fMRI) and neuropsychological examinations. The grey matter (GM) changes in PD patients were analyzed using voxel-based morphometry (VBM). The alterations in rCBF perfusion and functional connectivity (FC) among groups were then analyzed respectively. Additionally, correlations between these alterations and neuropsychological performances were further examined. Results: Compared to HC, the left caudate atrophy was detected in patients with PD. In comparison to both PD-NC and HC, patients with PD-MCI specifically exhibited hypoperfusion in the parietal memory network in the precuneus (PCu) and decreased PCu-FC in the right striatum controlled for brain atrophy. Moreover, PCu perfusion and PCu-FC strengths in the right striatum were positively associated with memory performance in PD-MCI. Conclusions: These findings suggest that the posterior parietal memory network dysfunction underlies memory deficits in PD-MCI.